2002
DOI: 10.1038/sj.hdy.6800131
|View full text |Cite
|
Sign up to set email alerts
|

Male fitness of oilseed rape (Brassica napus), weedy B. rapa and their F1 hybrids when pollinating B. rapa seeds

Abstract: The likelihood that two species hybridise and backcross may depend strongly on environmental conditions, and possibly on competitive interactions between parents and hybrids. We studied the paternity of seeds produced by weedy Brassica rapa growing in mixtures with oilseed rape (B. napus) and their F 1 hybrids at different frequencies and densities. Paternity was determined by the presence of a transgene, morphology, and AFLP markers. In addition, observations of flower and pollen production, and published dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 29 publications
9
54
0
Order By: Relevance
“…This, too, is a common result of competition studies (Table 3). Typically, hybrids of several crop-wild complexes, under at least some densities, tend to be more successful, although not superior, under interbiotype vs intrabiotype competition conditions (van Gaal et al, 1998;Pertl et al, 2002;Hauser et al, 2003;Al-Ahmad & Gressel, 2006). Although our analysis of variance was limited to two frequencies (50% and 100%), the path analysis confirmed this trend continues when hybrids are grown under other hybrid frequencies (33% and 66%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, too, is a common result of competition studies (Table 3). Typically, hybrids of several crop-wild complexes, under at least some densities, tend to be more successful, although not superior, under interbiotype vs intrabiotype competition conditions (van Gaal et al, 1998;Pertl et al, 2002;Hauser et al, 2003;Al-Ahmad & Gressel, 2006). Although our analysis of variance was limited to two frequencies (50% and 100%), the path analysis confirmed this trend continues when hybrids are grown under other hybrid frequencies (33% and 66%).…”
Section: Discussionmentioning
confidence: 99%
“…Superior performance of crop-wild hybrids has been detected in a few cases where fecundity, number of flowers, or aboveground biomass were used as estimates of lifetime fitness (Klinger & Ellstrand, 1994;Pertl et al ., 2002;Vacher et al ., 2004). Although examples of superior performance of hybrids are rare, a growing number of studies show that hybrid fitness depends on genotype, generation, and environment (Campbell et al ., 1998;Hauser et al ., 2003;Lexer et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent study, Hauser et al (1998b), found that a fitness penalty occurred in F 2 and backcrossed individuals, although a small percentage of hybrids were as fit as the weedy parent. The fitness of F 1 hybrids may also be frequency dependent (based on hybrid versus parent ratio), and the experimental design in future research may need to include the appropriate ratio of hybrid to parental weedy B. rapa plants to simulate selection for the hybrids with the highest fitness (Pertl et al 2002;Hauser et al 2003). Preliminary results from an experimental field study conducted in Ottawa, ON, in 2005 on two Canadian glyphosate resistant weedy B. rapa )B. napus BC 2 F 2 backcross hybrid populations under competitive field conditions (with vs. without wheat; weedy vs. weed-free) suggested that the hybrid is less fit than the parental weed population, regardless of the presence of the transgene (Warwick 2006).…”
Section: Female Parent)male Parent Citationmentioning
confidence: 99%
“…The first step in this introgression process would be formation of F 1 -hybrids. Frequencies of hybridisation with B. rapa as seed parent (~) has been reported by a number of authors (eg Landbo et al, 1996;Pertl et al, 2002;Warwick et al, 2003), rather than with B. napus as the seed parent (Jrgensen and Andersen, 1994). However, since hybridisation with B. napus as the seed parent is the transgene escape route for transplastomic varieties, it is important to estimate the extent of hybridisation in this cross.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of F 1 -hybrids among mother plants Hybridisation can be very genotype-dependent (Pertl et al, 2002). Thus, to minimise the 'genotype noise', we chose as B. napus (~) the variety Capitol, which should be homogenous because of its double-haploid origin.…”
Section: Johannessen Et Almentioning
confidence: 99%